Effects of Force in the Martian Plasma Environment With Solar Wind Dynamic Pressure Enhancement. Issue 3 (24th March 2023) - Song, Yihui; Lu, Haoyu; Cao, Jinbin; Li, Shibang; Yu, Yiqun; Wang, Siqi; Ge, Yasong; Zhang, Xiaoxin; Zhou, Chenling; Wang, Jianxuan
Abstract: Disturbed solar wind dynamic pressure is one of the important external drivers which could cause significant impacts on Martian plasma environment. In this study, a 3D multifluid multispecies numerical model is established to simulate the interaction between solar wind and Mars. Functions of electromagnetic forces applied on different ion species were analyzed. We found that the total electromagnetic force peaks near bow shock (BS) and magnetic pileup boundary (MPB) with clear asymmetry features, acting to decelerate solar wind plasma across boundary layers, and compresses heavy ions toward the planet inside the MPB. For solar wind protons, electron pressure gradient force dominates near BS and Hall electric field force dominates near MPB, controlling the location of plasma boundary. Furthermore, the morphology of motional electric field force shows clear north‐south asymmetry, leading to the formation of asymmetric structures and plasma flow in Martian space environment. The response of BS, MPB to a solar wind dynamic pressure enhancement event, as well as the effects of electromagnetic forces in this process are also investigated. After the arrival of solar wind pulse, the magnitudes of electromagnetic forces increased simultaneously to balance the enhanced solar wind dynamic pressure, while the peaks of forces moved inward with BS and MPB. The magnitudes and peaks of ion velocity in subsolar region show similar variations as well, with the greater enhancement of forces leading to the greater increase of ion velocities, indicating that the changes of forces influence boundary layers through the variation of plasma speed. Plain Language Summary: Variations of solar wind dynamic pressure can influence Martian space greatly. Long term solar wind events such as interplanetary coronal mass ejections, in which solar wind dynamic pressure enhanced significantly, can lead to the compression of Martian ionosphere/induced magnetosphere and facilitate ion escape on Mars. The supersonic solar wind creates a bow shock as the outmost boundary of Martian space environment, and the pileup of interplanetary magnetic field around Mars forms magnetic pileup boundary. A clear North‐South asymmetry feature forms for both plasma boundary and plasma flow. Using time dependent 3D multifluid MHD model, we investigate here the responses of boundary layers after encountering a solar wind pulse. In this way, the functions of electromagnetic forces in Martian space environment, as well as the possible mechanisms of the compression of boundary layers during solar wind dynamic pressure pulses are studied systematically for the first time. We found that the total electromagnetic force acts with magnetic pressure and thermal pressure to balance upstream solar wind near boundary layers. Also, it can be deduced that the immediate compression of boundary layers after solar wind dynamic enhancement can be attributed to the quick variations of electromagnetic force and plasma speed. Key Points: Functions of electromagnetic forces and the mechanisms of the variation of Martian plasma boundary are investigated by using MHD model Electromagnetic forces act to decelerate solar wind particles across the boundary layers, leading to asymmetric structures and plasma flow The short response time of plasma boundary is attributed to the quick variation of electromagnetic force and plasma speed